Datasets reflecting students' and teachers' views on the use of learning technology in a UK university. (September 2015) - Limniou, Maria; Downes, John J.; Maskell, Simon
Abstract Nowadays, the use of datasets is of crucial importance for the advancement of educational research. Specifically in the field of Higher Education, many researchers might share through online data repositories their research outputs in order for data to be reusable, accessible and accountable to educational community. The aim of this paper is to describe how web surveys along with the resultant datasets were created and how the datasets might be of some use to other researchers. The questionnaires are focused on examining teachers' and students' views about technology‐enhanced teaching and learning when using virtual learning environments (VLEs). The investigation was conducted across three Schools in the same University during the same time period. The datasets may assist other researchers in the development of further educational research concerning the use of technology resulting in more generalisable conclusions.